American Classics Evolutionary Perspectives - Saunders, Judith (Academic Studies Press, 2018)
This collection of essays offers evolutionary psychological analysis of selected works from the American literary tradition. Application of evolutionary theory to writing by Ben Franklin, Nathaniel Hawthorne, Mark Twain, Walt Whitman, Edith Wharton, F. Scot Fitzgerald, Zora Neal Hurston, and others creates an interdisciplinary framework for examining key textual features-plot, theme, tone, setting, symbol, characterization, point of view-and at the same time provides an accessible introduction to Darwinian literary critical methodology. Pertinent scientific research, together with essential terms and concepts, is explained in context. Connections are made throughout to existing commentary on the targeted texts, illustrating how Darwinian scrutiny can enrich, extend, or reconfigure understandings derived from other critical approaches.